Moral Values in Haris J and Maher Zain’s Song: A Semiotic Analysis - M. Afan; Nurul Wahidah; Nurmita Sari (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2025)
The aims of this research to accomplish three objects, the first is semiotic about sign or object, second is about the interpretant and the third is about Representamen. This thesis used semiotic theory by Charles Sunder Peairce which is analysis the sign. This research used a qualitative method. This research also focused with the signs in lyrics and Picture on video clips of both songs. The conclusions in this research are (1) Types of objects or sign there are Icon, Index and Symbol, (2) Types of Representments there are Dualizing, Sin sign and Leg sign, (3) Type of Interpretant there are Rheme, Deciding and Argument.